Attitudes of undergraduate business students toward sustainability issues. Issue 5 (7th September 2015) - Eagle, Lynne; Low, David; Case, Peter; Vandommele, Lisa
Abstract : Purpose: – This paper aims to report on findings from the first phase of a longitudinal study of undergraduate business students' attitudes, beliefs and perceptions concerning sustainability issues. Design/methodology/approach: – To improve understanding of the potential effects of changes in the curriculum, business students enrolled during the academic year prior to a redesigned, sustainability-informed, curriculum were surveyed. Familiarity with key sustainability terms was tested using a semi-structured questionnaire applied across two campuses of James Cook University, Australia. Quantitative data were complemented by use of open-ended questions that yielded qualitative insight into a range of student knowledge, attitudes, behaviours and normative influences relating to sustainability and climate change. Findings: – Findings reflect naïve awareness of the potential impact of individual contributions to sustainability and environmental challenges. They reveal a tendency to regard major issues as beyond personal control and to view solutions as being the responsibility of others. This is coupled with reluctance to consider major lifestyle changes. Social implications: – Universities are increasing their focus on sustainability-related issues and the ways in which these can be effectively communicated via curricula. This paper carries implications for this societal agenda, particularly in relation to the need to address disconnections between awareness of issues, personal relevance and effective strategies for addressing sustainability issues. Originality/value: – The findings shed fresh light on the attitudes and behavioural dispositions of undergraduate business students and could help guide the development and delivery of curriculum content.